Controversy regarding early specialization in athletics - Ababei, C.; Hagimã, M. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2017)
The International Association of Athletics Federations (IAAF) has promoted a series of international competitions starting with children III category, meaning children between 7 and 8 years old, which inevitably determined the lowering of the selection age to 5-6, very small ages in the context in which great performances in athletics appear after the age of 20. If 20 years ago, being an athlete at child II category meant to participate in national triathlon or tetrathlon competitions, today there is a specialization on events, starting with the age of 7, but also participation in international competitions. Here it is enough to mention the International Relay Competition, organized annually in Thessaloniki, Greece, where category III children participate in the 8x50 m relay (4F+4M), category II children in the 5x80m (male and female), and category I children in 4x200m relays (male and female). This study was based on the working hypothesis stating that the early specialization in athletics could reduce substantially the longevity of an athlete. Such an early specialization has raised, however, a number of controversies among coaches. In this sense, the research objective was to find out the Romanian coaches' opinion in regards to the individual event competitions for all children categories. The research methods used in this scientific endeavor were: the documentation method, the inquiry method, the observation method; the statistical-mathematical method of recording and interpreting the data.The study has confirmed partially the working hypothesis.